Bay-substituted octaazaperopyrenedioxides as solid-state emitters for strong light-matter coupling - Hertzog, Manuel; Eichelmann, Robert; Jeudy, Pierre; Wesp, Tobias; Ballmann, Joachim; Settele, Simon; Sebastian, Finn; Mischok, Andreas; Roux, Florian Le; Tenopala-Carmona, Francisco; Gather, Malte; Gade, Lutz H.; et al. (Journal of materials chemistry. C, Materials for optical and electronic devices, 2024)
Molecules based on the octaazaperopyrenedioxide (OAPPDO) motif represent a new class of organic emitters with the ability to form amorphous films when processed from solution while retaining their emissive properties. Here, we report the synthesis of bay-functionalized OAPPDO derivatives with thioether-substituents, which are structurally characterized by their twisted π-core. The combination of this structural motif with suitable substituents at the chromophore facilitates the deposition of neat and smooth films from solution, in which the molecules remain electronically decoupled, thus drastically reducing non-radiative decay pathways. An analysis of absorption and emission spectra of solutions and spincoated thin films is provided along with details of their structural morphology and thermodynamics. The amorphous thin films display spectroscopic characteristics similar to those of the isolated molecules in solution and exhibit photoluminescence quantum yields up to 17%. The high oscillator strength of smooth films of these OAPPDO derivatives enables their integration in Fabry-Pérot microcavities with high quality factors and the observation of strong light-matter coupling with clear exciton-polariton modes and large coupling strength.
Gesehen am 02.04.2025